SR-ND-PB ISOTOPIC COMPOSITIONS OF THE KOVDOR PHOSCORITE-CARBONATITE COMPLEX, KOLA PENINSULA, NW RUSSIA - Lee M.J.; Lee J.I.; Hur S.D.; Kim Y.; Moutte J.; Balaganskaya E. (My University, 2006)
The Sr, Nd and Pb isotopic compositions for the Kovdor phoscorite-carbonatite complex (PCC), Kola Peninsula, NW Russia, have been determined to characterize the mantle sources involved and to evaluate the relative contributions of a plume and subcontinental lithospheric mantle in the formation of the complex. The Kovdor PCC is a part of the Kovdor ultramafic-alkaline-carbonatite massif, and consists of six intrusions. The initial isotopic ratios of the analyzed samples, calculated at 380 Ma, display limited variations: εNd, + 2.0 to + 4.7; 87Sr/86Sr, 0.70319 to 0.70361 (εSr, - 12.2 to - 6.2); 206Pb/204Pb, 18.38 to 18.74; 207Pb/204Pb, 15.45 to 15.50; 208Pb/204Pb, 37.98 to 39.28. The Nd and Sr isotope data of the Kovdor PCC generally fit the patterns of the other phoscorites and carbonatites from the Kola Alkaline Province (KAP), but some data are slightly shifted from the mixing line defined as the Kola Carbonatite Line, having more radiogenic 87Sr/86Sr ratios. However, the less radiogenic Nd isotopic compositions and negative Δ7/4 values of Pb isotopes of the analyzed samples exclude crustal contamination, but imply the involvement of a metasomatized lithospheric mantle source. Isotopic variations indicate mixing of at least three distinct mantle components: FOZO-like primitive plume component, EMI-like enriched component and DMM-like depleted component. The isotopic nature of the EMI- and DMM-like mantle component observed in the Kovdor samples is considered to be inherited from metasomatized subcontinental lithospheric mantle. This supports the previous models invoking plume-lithosphere interaction to explain the origin of the Devonian alkaline carbonatite magmatism in the KAP. © 2006 Elsevier B.V. All rights reserved.
Keywords: CARBONATITE; FOZO; KOVDOR; PHOSCORITE; PLUME-LITHOSPHERE INTERACTION; SR-ND-PB ISOTOPE; Devonian; Paleozoic::Devonian; Палеозой::Девонская